Peranan Konten Digital Parenting di TikTok Sebagai Referensi Pola Asuh Orang Tua Milenial - Aljufri, Musa Kadzim (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2025)
In the digital age, the role of parents in child-rearing has become increasingly intricate with the rise of social media platforms such as TikTok. This study investigates the impact of Digital Parenting content from the TikTok account @rensia_sanvira on the parenting practices of millennial parents. The primary objective is to understand how such content influences contemporary parenting styles. Utilizing a descriptive qualitative research approach, the study incorporates content analysis, in-depth interviews, and textual analysis. Data was gathered through detailed interviews with millennial parents and by documenting content from @rensia_sanvira's TikTok account via screenshots. To ensure the validity of the data, source triangulation was employed. The results indicate that the Digital Parenting content provided by @rensia_sanvira has a positive influence on millennial parents, offering them valuable references and strategies for effective parenting. This study highlights the evolving role of social media in shaping parenting practices and underscores the importance of digital content in guiding modern parents.